The credible commitment problem and multiple armed groups: FARC perceptions of insecurity during disarmament in the Colombian peace process. Issue 4 (3rd July 2020) - Thomson, Andrew
ABSTRACT: Insecurities associated with the credible commitment problem during disarmament, demobilisation, and reintegration (DDR) processes are usually examined within a dyadic relationship between the government and a rebel group, ignoring how these insecurities play themselves out in the context of multiple warring parties. In addition, most studies on these dynamics take an overview macro-perspective, leaving out micro-dynamics such as how insecurity is experienced by those undertaking the disarmament process. This paper examines FARC members' perception of insecurity and threat during the disarmament process in Colombia in the context of multiple armed groups. Drawing on semi-structured interviews with FARC combatants in three different demobilisation camps during the process of disarmament, this paper sheds light on how credible commitment problems between the FARC and the Colombian government were influenced by the presence of additional armed actors and how associated insecurities are perceived by combatants who are disarming vis-à-vis various armed actors.